iPhone and iPad Apps for Absolute Beginners - Lewis, Rory. (Apress, 2010)
The iPhone is the hottest gadget of our generation, and much of its success has been fueled by the App Store, Apples online marketplace for iPhone applications. Over 1 billion apps have been downloaded in the 9 months the App Store has been open, ranging from the simplest games to the most complex business apps. Everyone has an idea for the next best-selling iPhone apppresumably thats why youre reading this now. And with the release of the iPad, this demand will just continue to grow. So how do you build an application for the iPhone and iPad? Dont you need to spend years learning complicated programming languages? What about Objective-C, Cocoa Touch, and the software development kit (SDK)? The answer is that you dont need to know any of those things. Anybody can start building simple applications for the iPhone and iPad, and this book will show you how. This book takes you to getting your first applications up and running using plain English and practical examples. It cuts through the fog of jargon and misinformation that surrounds iPhone and iPad application development, and gives you simple, step-by-step instructions to get you started. Teaches iPhone and iPad application development in language anyone can understand Provides simple, step-by-step examples that make learning easy Offers videos that enable you to follow along with the authorits like your own private classroom